2017
DOI: 10.1016/j.cell.2017.09.050
|View full text |Cite
|
Sign up to set email alerts
|

MHC-I Genotype Restricts the Oncogenic Mutational Landscape

Abstract: SUMMARY MHC-I molecules expose the intracellular protein content on the cell surface, allowing T cells to detect foreign or mutated peptides. The combination of six MHC-I alleles each individual carries defines the sub-peptidome that can be effectively presented. We applied this concept to human cancer, hypothesizing that oncogenic mutations could arise in gaps in personal MHC-I presentation. To validate this hypothesis, we developed and applied a residue-centric patient presentation score to 9,176 cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
378
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(400 citation statements)
references
References 42 publications
17
378
4
1
Order By: Relevance
“…This formulation of the PHBR-II score out-performed another scoring variation where peptides of varying lengths were considered (Figure S1). Two reasons contribute to the reduced performance relative to MHC-I (ROC AUC 0.75) (Marty et al, 2017). First, predicting single allele MHC-II binding has higher error than predicting single allele MHC-I binding (Andreatta et al, 2018; Paul et al, 2015; Wang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This formulation of the PHBR-II score out-performed another scoring variation where peptides of varying lengths were considered (Figure S1). Two reasons contribute to the reduced performance relative to MHC-I (ROC AUC 0.75) (Marty et al, 2017). First, predicting single allele MHC-II binding has higher error than predicting single allele MHC-I binding (Andreatta et al, 2018; Paul et al, 2015; Wang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This information is central to efforts to understand the role of the MHC in cancer evolution. To this end, we recently reported that MHC-I molecules play a significant role in shaping the mutational landscape of cancer (Marty et al, 2017). We demonstrated that mutations were more likely to be observed in tumors if the background MHC-I genotype resulted in poor affinity for peptides harboring the mutation, with implications for individual mutation probability and population mutation frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, driver mutations are actively selected, and expressed clonally and homogenously in cancers from many patients. Unfortunately, there have been very few driver mutations described as eliciting T cell responses, perhaps as a consequence of selection based on HLA genotype (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we hypothesized that patient-specific MHC-I variation would create individual differences in which cancer-causing mutations would be undetectable by the immune system and thus would drive tumorigenesis to clinically diagnosed disease. 5 To systematically evaluate this hypothesis, we established a score representing a patient's ability to expose a mutation on the cell surface for recognition by the immune system. Existing tools rank peptides based on their binding affinity to a single MHC-I allele.…”
Section: Introductionmentioning
confidence: 99%
“…6 We developed a Patient Harmonic-mean Best Rank (PHBR) score from ranked peptide binding affinities that accounts for the contribution of a patient's six MHC-I alleles and all possible peptides containing a specific residue, and validated it against mass spectrometry data for MHC-I alleles complexed with peptides. 5 Higher PHBR scores are interpreted as poorer MHC-I presentation and lower PHBR scores are interpreted as better MHC-I presentation.…”
Section: Introductionmentioning
confidence: 99%